2014
DOI: 10.1021/es5019652
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Clay Particles on the Transport and Retention of Titanium Dioxide Nanoparticles in Quartz Sand

Abstract: This study investigated the influence of two representative suspended clay particles, bentonite and kaolinite, on the transport of titanium dioxide nanoparticles (nTiO2) in saturated quartz sand in both NaCl (1 and 10 mM ionic strength) and CaCl2 solutions (0.1 and 1 mM ionic strength) at pH 7. The breakthrough curves of nTiO2 with bentonite or kaolinite were higher than those without the presence of clay particles in NaCl solutions, indicating that both types of clay particles increased nTiO2 transport in NaC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

5
46
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 115 publications
(54 citation statements)
references
References 59 publications
5
46
0
Order By: Relevance
“…They found that the mobility of TiO 2 was significantly reduced through soil columns especially in those porous media with higher concentrations of clay minerals. In contrast, Cai et al (2014) found that the presence of suspended clay particles (i.e., bentonite and kaolinite) facilitated the mobility of TiO 2 -NPs through quartz sand porous media.…”
Section: Introductionmentioning
confidence: 81%
See 3 more Smart Citations
“…They found that the mobility of TiO 2 was significantly reduced through soil columns especially in those porous media with higher concentrations of clay minerals. In contrast, Cai et al (2014) found that the presence of suspended clay particles (i.e., bentonite and kaolinite) facilitated the mobility of TiO 2 -NPs through quartz sand porous media.…”
Section: Introductionmentioning
confidence: 81%
“…Presence of clay particles in porous media is another influential parameter on NPs transport (Schroth and Sposito 1997;Vasiliadou and Chrysikopoulos 2011;Syngouna and Chrysikopoulos 2013;Cai et al 2014). Clay particles are the most abundant inorganic colloids in natural aquatic systems (Cai et al 2014) and there are approximately thirty different types (Wilson et al 2014).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, Liang et al (2013) studied the transport of Ag NPs and their interaction with clay particles in soils, and Cai et al (2014) discussed the combined effects of IS and clay particles on the transport of TiO 2 NPs in quartz sand. These studies mainly focused on the effect of pH, IS and clay particles, but some studies show that NOM also plays an important role in the stability of NPs, such as stabilization due to the adsorption of NOM, or enhanced coagulation due to the bridging effect of NOM (Chen and Elimelech, 2007a;Mohd Omar et al, 2014;Zhu et al, 2014).…”
mentioning
confidence: 99%